2015
DOI: 10.1007/s10340-015-0675-x
|View full text |Cite
|
Sign up to set email alerts
|

Myco-synthesis of silver nanoparticles using Metarhizium anisopliae against the rural malaria vector Anopheles culicifacies Giles (Diptera: Culicidae)

Abstract: Each year, mosquito-borne diseases infect nearly 700 million people, resulting more than one million deaths. In this study, we proposed a Metarhizium anisopliae-based method of green synthesis of silver nanoparticles to control the rural malaria vector Anopheles culicifacies. Silver nanoparticles were characterized by UV–Vis spectroscopy, Fourier transform infrared spectroscopy, scanning electron microscopy, energy-dispersive X-ray analysis, and X-ray diffraction. In acute toxicity experiments, larvae (I–IV in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
43
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 121 publications
(52 citation statements)
references
References 57 publications
5
43
0
Order By: Relevance
“…4). The present finding corroborates previous reports on AgNP biosynthesis using botanical and microbial products [3,43,[50][51][52]67]. XRD patterns showed intense peaks corresponding to the (111), (200), (220), (311) and (222) sets of lattice planes (Fig.…”
Section: Characterization Of Silver Nanoparticlessupporting
confidence: 82%
See 1 more Smart Citation
“…4). The present finding corroborates previous reports on AgNP biosynthesis using botanical and microbial products [3,43,[50][51][52]67]. XRD patterns showed intense peaks corresponding to the (111), (200), (220), (311) and (222) sets of lattice planes (Fig.…”
Section: Characterization Of Silver Nanoparticlessupporting
confidence: 82%
“…The biological synthesis of metal nanoparticles is a research area currently considered more ecofriendly and cost-effective, if compared to other chemical and physical methods [3,11]. Nano-technology is envisaged to be the next frontier in the ongoing development of cancer therapy [22,35] as researchers in the biomedical and material engineering fields are working together to discover the possibility of using nano-materials as novel tools for medical sciences.…”
Section: Introductionmentioning
confidence: 99%
“…The plant-mediated biosynthesis (i.e., Bgreen synthesis^) of nanoparticles is advantageous over chemical and physical methods, since it is cheap, single-step, does not require high pressure, energy, temperature, and the use of highly toxic chemicals (Sinha et al 2009). In particular, a growing number of plants and fungi have proposed for efficient and rapid extracellular synthesis of silver and gold nanoparticles (see Benelli 2015c for a recent review), which showed excellent mosquitocidal properties, also in field conditions (e.g., Arjunan et al 2012;Roni et al 2013;Amerasan et al 2015;Dinesh et al 2015;Murugan et al 2015a, b, c, d;Sujitha et al 2015;Suresh et al 2015).…”
Section: Introductionmentioning
confidence: 97%
“…Further research on ovicidal products of natural origin is needed to outline concrete implications for Culicidae control, with special reference to the following points: (a) chemical characterization, identification, and standardization of plant-borne ovicides (Heng et al 2013); (b) description of the mechanism(s) of biotoxicity against mosquito eggs; (c) evaluation of industrial by-products of plant origin as ovicides against mosquitoes of medical importance (e.g., neem cake, see Benelli et al 2014Benelli et al , 2015b; (d) field evaluation of ovicidal properties of botanical products against day-biting mosquitoes; (e) biosynthesis of ovicidal nanoparticles using plant extracts, and evaluation of their impact on non-target mosquito natural enemies (Benelli 2015b). Indeed, the reducing potential of plant-borne compounds can be used to produce metal nanoparticles with excellent mosquitocidal properties (e.g., Amerasan et al 2015;Dinesh et al 2015;Murugan et al 2015b, c, d, e;Sujitha et al 2015;Suresh et al 2015). Due to simplicity, low cost involvement, and zero contamination, the Bgreen synthesis^of nanoparticles recently emerged as one of the most active areas of current nanotechnology research (Rajan et al 2015).…”
Section: Discussionmentioning
confidence: 99%